Studies of the effect of melt spinning on the electrochemical properties of the AB2 Laves phase alloys - Ika Dewi Wijayanti; Live Mølmen; Roman Denys; Matylda N Guzik; Stéphane Gorsse; Jean Louis Bobet; Volodymyr Yartys (JMES The International Journal of Mechanical Engineering and Sciences, 2021)
A comparative study of the effect of melt spinning on the electrochemical properties of the C14 and C15 AB2 alloys has been performed. The wheel speeds of 630, 2100, and 4100 cm/s were applied during the rapid solidification of both alloys. The structural analysis of the formed phases was performed by X-ray powder diffraction (XRD), while their microstructural morphology was studied by scanning electron microscopy (SEM). In both alloys a tremendous grain refinement due to the melt spinning process was observed: In addition, melt spinning also significantly contributed to the morphological variation of the microstructural changes in C14 alloys which showed changes from the equiaxed grain at lower speed to the small dendrites at higher speed. In contrast to the C14 alloys, the morphological variation was not observed for the C15 alloys. Furthermore, for both C14 and C15 alloys melt-spun at 2100 cm/s the maximum capacities of 435 and 414 mAh/g were achieved, respectively. As both alloys revealed the significant grain refinement due to the melt spinning, an increase in electrochemical capacity was achieved. However, the melt spinning parameters need to be further optimized to improve poor activation behavior of the rapidly solidified alloys.